“Tirto Mekar Tani” Tamantirto Kasihan Bantul Women's Farming Group Empowerment Through Bedog Riverbank Space Utilization: Pemberdayaan Kelompok Wanita Tani “Tirto Mekar Tani” Tamantirto Kasihan Bantul Melalui Pemanfaatan Ruang Bantaran Sungai Bedog - Umul Aiman; Bambang Sriwijaya; Dian Astriani; Eukarista Alun (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
The women's farmer group (KWT) "Tirto Mekar Tani" in Tamantirto, Kasihan, Bantul, has little or no knowledge about organic farming, depending on synthetic fertilizers and chemical pesticides. On the other hand, partners have a very high cultivation spirit to fill their free time. This community service activity aims to empower partners by utilizing riverbanks in the area. The activity is expected to have a positive impact on environmental health and can increase group income, at least at the family level. The implementation of the activity includes identification and collection of initial data, formation of a work team, counseling and training, planning a space utilization program, monitoring and evaluation, documentation and publication of results. The results of the activity show the high enthusiasm of partners in planting organic vegetables, having knowledge of organic vegetable cultivation, fertile vegetable growth and satisfactory harvest results, increasing the beauty of the environment and strengthening friendships between members. The profits from the sale of vegetables after being consumed by members are used to rent village-owned ponds for tilapia cultivation, thus contributing to improving community welfare.